Metabolic and cellular alterations underlying the exaggerated renal prostaglandin and thromboxane synthesis in ureter obstruction in rabbits. Inflammatory response involving fibroblasts and mononuclear cells. - Okegawa, T (1983)
Unilateral ureter obstruction in rabbits produced profound changes in endogenous and exogenous renal arachidonic acid metabolism. Isolated perfused hydronephrotic kidneys (removed after 3 or 10 d of ureter obstruction) responded to bradykinin stimulation with a markedly enhanced release of prostaglandin E2 and thromboxane A2. Reversal (3 or 10 d) of the ureter obstruction resulted in a reduction in the vasoactive peptide-induced release of prostaglandin E2 and thromboxane A2 from the perfused hydronephrotic kidney. However, postobstruction reversal of prostaglandin production by the agonist-stimulated perfused kidney was not reflected in the cortical microsomal cyclooxygenase activity, which is greatly enhanced during ureter obstruction and does not decrease after removal of the obstruction. Histological analysis of the renal cortex in rabbits with ureteral obstruction revealed a proliferation of fibroblast-like cells and the presence of mononuclear cells; removal of the obstruction did not result in a disappearance of cortical fibroblasts but did result in a decrease of monocytes. The critical involvement of mononuclear cells in the exaggerated arachidonate metabolism that occurs during hydronephrosis was exhibited by the demonstration that: (a) only the perfused hydronephrotic rabbit kidney responded to administration of endotoxin with a sustained release of prostaglandin E2 and thromboxane A2; (b) the contralateral rabbit kidney, which is devoid of mononuclear cells, did not respond to endotoxin; and (c) the hydronephrotic cat kidney, which exhibits a fibroblast proliferation with a low number of mononuclear cells, did not respond to endotoxin. Thus, proliferation of fibroblast-like cells and the presence of mononuclear cells appear to be involved in the exaggerated prostaglandin and thromboxane production underlying hydronephrosis. The increase in microsomal cyclooxygenase activity is apparently most closely correlated with the increased fibroblastic activation and cellularity, whereas mononuclear cells (possibly via monokines) seem to be critical for the markedly enhanced prostaglandin and thromboxane release induced by endotoxin and bradykinin.